Survey of the spatial distribution of bats according to type and positive for rabies in Botucatu-SP the period 2006 to 2011 - Langoni, H.; Menozzi, B. D.; Vitória, C. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Bats are considered to be the man transmitters and disseminators of rabies virus in Brazil’s urban centers, particularly in regions where canine rabies has been controlled. This brings up a great fear for the public health authorities in the country about this disease, which would be the possible reintroduction of rabies in domestic animals due to easier interaction with the bats, and also from contact with humans. Clearly increasing the number of cases of various species of bats that were diagnosed as positive for rabies throughout the country especially in the state of São Paulo. The municipality of Botucatu – SP is located in the midwestern region and is located at 22 53 09 south latitude and 48 26 42 west longitude, 804 meters above sea level, and makes an important surveillance work, since 2003, where animals are collected on public roads or residences and then are submitted for diagnosis at Faculty of Veterinary Medicine and Animal Science of UNESP, Botucatu, where is installed the Zoonosis Diagnostic Laboratory. Among theirs 2006 and 2011 where received 984 bats for diagnosis, being in 2006, 278 bats, 182 in 2007, 115 in 2008, 116 in 2009, 166 in 2010 and 127 in 2011. Only in 2008 and 2011 did not find positive for rabies bats. In others years there were 11 positive diagnoses, characterized at least three genres: Artibeus, Myotis and Nyctinomops and two species, Artibeus lituratus and Myotis nigricans. The positive bats (all non-hematophagous) are distributes in the central part of the city, in areas whit large trees, two creeks that surround the city. In the spatial distribution of species in the country, we find the homogeneous distribution of at least 40 genus/species of bats, being the most frequent 55% (557) belonging to the genus Molossus, including species Molossus molossus and Molossus rufus, distributed in equal uniformity throughout the municipality. Revealing that although this distribution, and the large number of genera/species involved, the virus is restricted to only five genera/species, also restricted to the central area of the municipality. Also important to highlight the nonpositivity of the bats of the genus Molossus, despite being the greater quantity and better distributed by county.